Photon activation analysis of metallurgical tap smelting slag using a high energy medical accelerator: Further studies - Togia, N.; Vasilopoulou, T.; Filippaki, E.; Georgolopoulou, P.; Mertzimekis, T. J.; Basiakos, Y.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2019)
N/A